2001
DOI: 10.1080/003655201750305404
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Markers for Barrett’s Esophagus and Associations to Esophageal Z-Line Appearance

Abstract: CK7/20 is a feasible marker for Barrett's esophagus. Intestinal metaplasia in different ZAP grades differs regarding expression of immunohistochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“…The immunostaining pattern has a strong, diffuse CK7 staining of the surface and glandular epithelium, and weak CK20 staining of the superficial epithelium (18). While these results were confirmed by later reports (1,19), they were not reproducible by others (3,20).…”
contrasting
confidence: 29%
“…The immunostaining pattern has a strong, diffuse CK7 staining of the surface and glandular epithelium, and weak CK20 staining of the superficial epithelium (18). While these results were confirmed by later reports (1,19), they were not reproducible by others (3,20).…”
contrasting
confidence: 29%
“…Ormsby et al found that a BE CK 7/20 staining pattern was highly sensitive and specific for BE compared to gastric IM, and suggested that immunostaining may be useful to differentiate metaplastic columnar epithelium in the esophagus related to BE from chronic gastritis with IM in biopsies from the GEJ region. However, several other workers have not been able to confirm the findings by Ormsby et al, and instead, have shown that the CK 7/20 immunostaining profile in biopsies from the GEJ often show a BE pattern (23,27,90). For instance, in a biopsy study by Glickman et al, patients with long-segment BE, short-segment BE, IM of the GEJ secondary to either H. pylori or GERD, or with a normal gastric antrum, had a BE CK 7/20 staining pattern in 91% of BE cases, 90% of IM of the GEJ cases (regardless of the etiology), and in 14% of gastritis cases secondary to H. pylori (27).…”
Section: Differential Diagnosis Of H Pylori-induced True Gastric Carmentioning
confidence: 46%
“…For instance, in a biopsy study by Glickman et al, patients with long-segment BE, short-segment BE, IM of the GEJ secondary to either H. pylori or GERD, or with a normal gastric antrum, had a BE CK 7/20 staining pattern in 91% of BE cases, 90% of IM of the GEJ cases (regardless of the etiology), and in 14% of gastritis cases secondary to H. pylori (27). Others have also shown mixed results with CK 7/20 immunostaining (13,23,(90)(91)(92).…”
Section: Differential Diagnosis Of H Pylori-induced True Gastric Carmentioning
confidence: 96%
“…Columnar Barrett's epithelium exhibits enterocytic differentiation as evidenced by its expression of proteins associated with intestinal mucosal function, such as sucrase-isomaltase, cytokeratins, and mucins (22)(23)(24)(25). We found that in Barrett's epithelia from which cancer had arisen the predominant change in gene expression was down-regulation of differentiation-specific genes involved in gastrointestinal mucosal functions, such as transport, metabolism, and mucous secretion.…”
Section: Gene Expression In Esophageal Adenocarcinomamentioning
confidence: 76%